Strategic lockdown and blessing variation – potential success keys against COVID-19 - Bhattacharjee, Koutilya; Saha, Suvajit; Banerjee, Emili; Ganguly, Partha (Asian Journal of Medical Sciences, 2020)
Background: COVID-19, a respiratory illness, has become a pandemic originating from the Wuhan city of China. Earlier, similar diseases like Severe Acute Respiratory Syndrome and Middle East Respiratory Syndrome had caused mass mortality in different parts of the globe. Therefore, a similar new disease was of great concern for the humankind. However, it is observed that COVID-19 has a differential rate disease prevalence and mortality among the countries. Aims and Objective: This disease has already affected 2.4 million people globally, leading to healthcare disasters, financial meltdowns due to worldwide lockdowns. Our objective was to evaluate the effect of lockdown in India and to characterize the functional implications of genetic variations of SARS-CoV-2 (the causative virus). Materials and Methods: Epidemiological data for COVID-19 was taken from WHO and other national or international bodies to evaluate the prevalence of the disease in different countries. A statistical modeling was done to estimate the probable number of COVID-19 affected persons with or without lockdown. Bioinformatic analyses were done to identify mutational variations of SARS-CoV-2 and their functional implications. Results: Statistical modeling predicted that number of COVID-19 case could be much higher without lockdown in countries. Countries with malaria and dengue prevalence are less affected by COVID-19. Bioinformatic analyses revealed presence of an Indian SARS-CoV-2 SP1 variant with lesser capability of human receptor binding. Conclusion: Lockdown and deliberate testing has played key important role in prevention of disease transmission. Indian variant of SARS-CoV-2 with less affinity towards human receptor may have a role for lesser virulence.